Pygmy grasshoppers (Orthoptera: Tetrigidae) of Vietnam: the genus Bolivaritettix Günther, 1939 - Storozhenko, Sergey Yu. (Zootaxa, 2018)
Vietnamese species of the genus Bolivaritettix Günther, 1939 are reviewed and illustrated. Altogether ten species are reported from Vietnam, of which five are new to science, namely—B. abruptus sp. nov., B. anaglypticus sp. nov., B. constrictus sp. nov., B. similis sp. nov., and B. vietnamensis sp. nov., while three species, B. sculptus (Bolívar, 1887), B. humeralis Günther, 1939 and B. celaenotus Zheng, Zhang et Dang, 2009, are recorded from Vietnam for the first time. A key to Vietnamese species is provided.